The effect of possible EU diversification requirements on the risk of banks' sovereign bond portfolios - Ben R. Craig; Margherita Giuzio; Sandra Paterlini (European Central Bank (ECB), 2020)
Recent policy discussion includes the introduction of diversification requirements for sovereign bond portfolios of European banks. In this paper, we evaluate the possible effects of these constraints on risk and diversification in the sovereign bond portfolios of the major European banks. First, we capture the dependence structure of European countries' sovereign risks and identify the common factors driving European sovereign CDS spreads by means of an independent component analysis. We then analyse the risk and diversification in the sovereign bond portfolios of the largest European banks and discuss the role of bias", i.e. the tendency of banks to concentrate their sovereign bond holdings in their domicile country. Finally, we evaluate the effect of diversification requirements on the tail risk of sovereign bond portfolios. Under our assumptions about how banks rebalance their portfolio to respond to the new requirements, demanding that banks modify their holdings to increase their portfolio diversification may be ineffective in reducing portfolio risk, including tail risk.
Keywords: G01; G11; G21; G28; 330; Bank regulation; sovereign-bank nexus; sovereign risk; home bias; diversification